Single nucleotide variants in the protein C pathway and mortality in dialysis patients. - Gürbey Ocak; Christiane Drechsler; Carla Y Vossen; Hans L Vos; Frits R Rosendaal; Pieter H Reitsma; Michael M Hoffmann; Winfried März; Willem H Ouwehand; Raymond T Krediet; Elisabeth W Boeschoten; Friedo W Dekker; et al. (PLoS ONE)
Background The protein C pathway plays an important role in the maintenance of endothelial barrier function and in the inflammatory and coagulant processes that are characteristic of patients on dialysis. We investigated whether common single nucleotide variants (SNV) in genes encoding protein C pathway components were associated with all-cause 5 years mortality risk in dialysis patients. Methods Single nucleotides variants in the factor V gene (F5 rs6025; factor V Leiden), the thrombomodulin gene (THBD rs1042580), the protein C gene (PROC rs1799808 and 1799809) and the endothelial protein C receptor gene (PROCR rs867186, rs2069951, and rs2069952) were genotyped in 1070 dialysis patients from the NEtherlands COoperative Study on the Adequacy of Dialysis (NECOSAD) cohort) and in 1243 dialysis patients from the German 4D cohort. Results Factor V Leiden was associated with a 1.5-fold (95% CI 1.1-1.9) increased 5-year all-cause mortality risk and carriers of the AG/GG genotypes of the PROC rs1799809 had a 1.2-fold (95% CI 1.0-1.4) increased 5-year all-cause mortality risk. The other SNVs in THBD, PROC, and PROCR were not associated with 5-years mortality. Conclusion Our study suggests that factor V Leiden and PROC rs1799809 contributes to an increased mortality risk in dialysis patients.